Optimisme dan Efikasi Diri Pengambilan Keputusan Karir pada Mahasiswa Program Diploma III Kebidanan - Farhanita Riziq; Sugiarti A. Musabiq (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: The high rate of maternal mortality and the mortality rate of infants in Indonesia makes Indonesia’shealth minister, in his decision, determined that midwives are the main line for reducing MMR and IMR. Unfortunately, in the effort to become a midwife, there are many challenges that must exist, such as, the difficulty of STRand the existence of unemployment phenomenon. These conditions ultimately affect the optimism of midwiferystudents in determining their career choices in the future.Objective: to see whether there is a relationship between optimism and career decision self-efficacy in the DiplomaIII Midwifery students program in Indonesia.Methods: Participants in this study were students of Diploma III midwifery level 2 and 3 who required 571 peoplefrom A and B accredited midwifery academies in DKI Jakarta, Banten, West Java and West Sumatra provinces. Thisresearch is a research with correlational research design. The sampling technique used is convenience sampling.Results: The results of this study indicate a significant positive relationship between optimism and career decisionself-efficacy (r = + 203, n = 571, p <.01, two tails). There are other findings of life satisfaction, contextual aspects,self-support, high predictors or low career decision self-efficacy score.Conclusion: There is a positive and significant relationship between optimism and career decision self efficacy.It means that the higher the score of individual optimism, the higher the career decision self-efficacy score. Conversely, the lower the individual’s optimism score, the lower the career decision self-efficacy scoreKeywords: Career decision self-efficacy; Midwifery college student; Optimism